Use of Cashless Payment and Its Implications for Impulsive Buying: Examining Consumer Behavior Patterns in the Digital Era in E-Commerce - Fitriyani; Afrizal, Yogi Hady (SENTRALISASI, 2025)
This research aims to determine consumer behavior patterns in using non-cash payments and the implications for impulsive purchases in e-commerce. This research uses qualitative methods to gain in-depth insight from each informant, so the Unified Theory of Acceptance and Use of Technology (UTAUT2) approach was chosen to determine this pattern. The research results reveal that the convenience offered by non-cash payments accelerates a person's decision making when shopping, which encourages impulsive buying behavior where shopping decisions are taken quickly without planning. The implication of this research is that the development of cashless payments not only provides practical benefits in daily transaction activities, but also creates new shopping patterns that combine convenience and psychological encouragement through promotional offers. This shows how digitalization in payment methods is not just a means of payment but also a means of influencing consumer behavior in the current digital era.